Development of Creative Economy Based on Small and Medium Micro Enterprises: A Systematic Literature Review - Effendy, Aidil Amin; Sunarsi, Denok; Mulyad, Mulyad; Hastono, Hastono; Nurhadi, Ahmad (Universitas Pamulang, 2024)
The aim of this research isto knowDevelopment of Micro, Small and Medium Enterprises Based on Creative Economy in the Current Competitive Era and MSME Development Strategy in the Competitive Era. This research uses a descriptive exploratory approach using a literature review or library study approach, namely referring to various literature, such as books, dissertations, scientific journals and the internet.Research resultIt can be concluded that there is a need for the creative economy to be improved because of its positive influence on the economy in Indonesia. Thus, it can be said that the growth and improvement of the creative economy industry can continue to help the economy in Indonesia.So the development of creative economy-based Micro, Small and Medium Enterprises (MSMEs) needs to be supported in the current competitive era. Strategy in Developing MSMEs in the Competitive Eraaccording to the author based on analysis of various literature, including, namelyDoCollaboration with various parties to support the success of MSMEs, the need for government and private support in developing MSMEs,Improving the quality of MSME actors in utilizing technology,Carrying out online marketing and promotions to increase sales of MSMEs, training is needed for the development of MSMEs and human resource development or MSME actors in the creative economy industry. MSMEs can consistently develop if the actors continue to develop themselves to be able to compete in the current competitive era.